2019
DOI: 10.3390/ani9090601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Farming Conditions on the Rumen of Red Deer (Cervus elaphus)

Abstract: Simple SummaryThe diet offered to an animal in captivity may considerably differ from the natural one; this can affect the development of the digestive system, with connected influence on the health condition and welfare of the animal. Through a comparison of morphological and environmental characteristics of the rumen of red deer, we found out that, during autumn season, farmed deer have a limited choice of diet compared to wild ones living in the forest; this condition affected the morphology of the rumen wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
1
9
1
1
Order By: Relevance
“…As a general agreement, the papillary size is associated with the absorption capacity, which occurs in a large amount of rich in carbohydrate diet, resulting in excessive VFA concentration and low pH (de Resende-Junior et al, 2006). Mason et al (2019) reported that farmed deer have lesser papillae characteristics than wild deer, slightly different from the current study. The evaluation of the absorptive and motility capacities is required for macro and micro levels to support our findings as suggested by Consalvo et al (2016) that microscopic evaluation gave a better description of rumen mucosae morphology.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As a general agreement, the papillary size is associated with the absorption capacity, which occurs in a large amount of rich in carbohydrate diet, resulting in excessive VFA concentration and low pH (de Resende-Junior et al, 2006). Mason et al (2019) reported that farmed deer have lesser papillae characteristics than wild deer, slightly different from the current study. The evaluation of the absorptive and motility capacities is required for macro and micro levels to support our findings as suggested by Consalvo et al (2016) that microscopic evaluation gave a better description of rumen mucosae morphology.…”
Section: Discussioncontrasting
confidence: 99%
“…At the same time, the pH also changed accordingly. Thus, feed consumed in the rearing practices significantly influences rumen physiology (Diao et al, 2019;Ferreira et al, 2017;Kay et al, 1980;Steele et al, 2011) and the digestive morphology of the ruminants (Mason et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Captive lions Panthera leo fed soft foods exhibit smaller mandibular and maxillary regions of the skull and weaker bite force than wild conspecifics (Zuccarelli, 2004). Diets in captivity also change gastrointestinal organ morphology, including the rumen (Mason et al ., 2019), length of the intestines and other digestive organs (Moore & Battley, 2006), kidney and spleen mass (Courtney Jones, Munn & Byrne, 2018). There is also evidence that the brains of fish (Kihslinger, Lema & Nevitt, 2006; Marchetti & Nevitt, 2003; Mayer et al ., 2011), birds (Guay & Iwaniuk, 2008; Smulders et al ., 2000) and mammals (Kruska, 1996) decrease in size in captivity relative to wild conspecifics, but how these changes affect cognition and behaviour is unclear.…”
Section: The Captive Phenotypementioning
confidence: 99%
“…Secondly, these studies are based in controlled farm environments, where animals are on strictly regimented diets [3,4]. Therefore, it is no surprise that these studies may not realistically depict rumen condition in an uncontrolled or wild setting, especially in non-traditional farming species, such as deer [5]. Hence, studies performing exploratory assessment of the rumens of wild ruminants are currently needed to fill this fundamental gap in the literature.…”
Section: Introductionmentioning
confidence: 99%